Pengaruh Intensitas Kegiatan Salafiyah Terhadap Keberlangsungan Pendidikan Formal di Pondok Pesantren Sunniyah Salafiyah Putri Al-Azhar - Elvina Damayanti, Putri; Halimah, Siti; Zidniyati (AL MURABBI, 2025)
Salafiyah Islamic boarding schools are traditional Islamic educational institutions that prioritize the study of classical Islamic texts through methods such as sorogan and bandongan. In recent years, many pesantren have integrated formal education into their systems while maintaining traditional values. This study examines the influence of salafiyah pesantren on the existence of formal education at the Sunniyah Salafiyah Pesantren Al-Azhar Putri. The research focuses on how pesantren values, learning methods, and institutional structures affect students’ participation in formal education and how both systems are integrated in daily practice.The study used a descriptive quantitative approach with an alternative hypothesis stating that salafiyah pesantren influence formal education, while the null hypothesis states otherwise. Purposive sampling was applied to select 42 SMA and SMK female students as respondents. Data were collected through questionnaires and analyzed using descriptive and regression analysis.The results indicate that salafiyah pesantren have a significant positive effect on the existence of formal education. The simple linear regression equation obtained was Y = 68.385 + 0.465X. The influence of salafiyah pesantren on formal education reached 45.6%, while 54.4% was affected by other factors. The findings also show that the learning system at Sunniyah Salafiyah Pesantren Al-Azhar Putri supports students positively. Formal education in the pesantren environment successfully integrates tarbiyyah, ta’lim, and ta’dib to strengthen both religious character and academic development. These findings confirm that traditional pesantren values and modern schooling can coexist harmoniously to create balanced religious, social, and intellectual development for female students